2021
DOI: 10.1007/s00338-021-02088-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure-from-Motion on shallow reefs and beaches: potential and limitations of consumer-grade drones to reconstruct topography and bathymetry

Abstract: Reconstructing the topography of shallow underwater environments using Structure-from-Motion—Multi View Stereo (SfM-MVS) techniques applied to aerial imagery from Unmanned Aerial Vehicles (UAVs) is challenging, as it involves nonlinear distortions caused by water refraction. This study presents an experiment with aerial photographs collected with a consumer-grade UAV on the shallow-water reef of Fuvahmulah, the Maldives. Under conditions of rising tide, we surveyed the same portion of the reef in ten successiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…The method developed also has operational limitations. The study further confirmed the importance of the underwater photogrammetric control network included in the study [70]. However, in some cases, the assumption of such a photogrammetric control network may prove problematic.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The method developed also has operational limitations. The study further confirmed the importance of the underwater photogrammetric control network included in the study [70]. However, in some cases, the assumption of such a photogrammetric control network may prove problematic.…”
Section: Discussionsupporting
confidence: 73%
“…An additional constraint is the noticeable decrease in accuracy with increasing depth, water turbidity, and diverse bottom material [61]. The research undertaken presents a photogrammetric approach that confirms the possibility of obtaining data using an underwater photogrammetric control network [70] and fills the gap in coastal water mapping where the opportunities for obtaining bathymetric data with passive remote sensing sensors are significantly limited. The need to create hybrid methods using hydrographic and optical methods was pointed out in [13].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…It has become the basis for recognizing that an autonomous unmanned system for bathymetric monitoring of shallow waterbodies can be developed using the currently available research tools. However, bathymetry estimation methods are subject to errors (non-linear distortions) due to the wave refraction phenomenon [34] that occurs in the water environment, so it is necessary to eliminate the refraction effect at the water-air interface in the photogrammetric processing [35]. The decisive solutions enabling a positive conclusion of the proposed study include:…”
mentioning
confidence: 99%